Interaction between nasal epithelial cells and Tregs in allergic rhinitis responses to allergen via CCL1/CCR8 - Sha, Jichao; Yang, Maolin; Lei, Yashu; Sun, Liwei; Meng, Cuida; Zhu, Dongdong (Frontiers in Immunology, 2025)
BackgroundThe airway epithelial barrier is the first defence against aeroallergens. Nasal epithelial cells (NECs) are vital in regulating innate and adaptive mucosal immunity in allergic rhinitis (AR). Tregs produce cytokines essential for the immunomodulatory activities in allergen immunotherapy. Understanding the relationship between NECs and Tregs in the airway hyperresponsiveness network is essential for developing novel treatments.MethodsUsing an in vitro human Treg-NEC co-culture system of AR and health control group, the chemokine expression profiles of NECs were examined using immunohistochemistry, RT-PCR, and ELISA, and functional surface markers of Tregs were detected using flow cytometric analysis. Correlation analysis was performed between cytokines derived from NECs and surface markers of CD4+CD8+Foxp3+ Tregs in the AR group after co-culture, including TSLP/CTLA4, CCL1/CTLA4, TSLP/CTLA4, TSLP/CCR8, and CCL1/CCR8.ResultsCCR8 and CTLA-4 expressions after co-culturing were higher than single culture. Following Derp1 stimulation, TSLP, IL-25 and TGF-β expressions in the AR + Derp1 group were increased. CCL1 mRNA was lower in the AR + Derp1 group than control group. In the AR + Derp1 group, TSLP was higher, and CCL1 protein levels were decreased. There were no significant differences in IL-25, TGF-β and IL-10. When Treg co-culture group added, changes were similar to that observed in pNECs. After co-culture, CCL1/CCR8 was positively correlated in AR.ConclusionHuman pNECs can communicate with Tregs directly, CCL1/CCR8 may be the pathway between NECs and Tregs in vitro and may play a key role in the immune network of AR.